Risk Predictors and Causes of Technique Failure Within the First Year of Peritoneal Dialysis: An Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) Study - See, Emily J.; Johnson, David W.; Hawley, Carmel M.; Pascoe, Elaine M.; Badve, Sunil V.; Boudville, Neil; Clayton, Philip A.; Sud, Kamal; Polkinghorne, Kevan R.; Borlace, Monique; Cho, Yeoungjee (American journal of kidney diseases, 2018)
Concern regarding technique failure is a major barrier to increased uptake of peritoneal dialysis (PD), and the first year of therapy is a particularly vulnerable time. A cohort study using competing-risk regression analyses to identify the key risk factors and risk periods for early transfer to hemodialysis therapy or death in incident PD patients. All adult patients who initiated PD therapy in Australia and New Zealand in 2000 through 2014. Patient demographics and comorbid conditions, duration of prior renal replacement therapy, timing of referral, PD modality, dialysis era, and center size. Technique failure within the first year, defined as transfer to hemodialysis therapy for more than 30 days or death. Of 16,748 patients included in the study, 4,389 developed early technique failure. Factors associated with increased risk included age older than 70 years, diabetes or vascular disease, prior renal replacement therapy, late referral to a nephrology service, or management in a smaller center. Asian or other race and use of continuous ambulatory PD were associated with reduced risk, as was initiation of PD therapy in 2010 through 2014. Although the risk for technique failure due to death or infection was constant during the first year, mechanical and other causes accounted for a greater number of cases within the initial 9 months of treatment. Potential for residual confounding due to limited data for residual kidney function, dialysis prescription, and socioeconomic factors. Several modifiable and nonmodifiable factors are associated with early technique failure in PD. Targeted interventions should be considered in high-risk patients to avoid the consequences of an unplanned transfer to hemodialysis therapy or death.